Efficacy of oleandrin and PBI-05204 against viruses of importance to commercial pig health management - Newman, Robert A.; Abdelsalam, Karim; Buterbaugh, Robin; Sastry, K. Jagannadha (Frontiers in Animal Science, 2024)
Background Infection by porcine respiratory and reproductive syncytial virus (PRRSV), swine influenza virus (SIV) and porcine epidemic diarrhea (PEDV) adversely affect worldwide pig production. Because effective control remains elusive the present research was designed to explore the in vitro antiviral activity of oleandrin and an N. oleander extract (PBI-05204) against each porcine virus. Methods Monkey kidney (MARK-145) cells, Madin-Darby canine kidney cells (MDCK), and African green monkey kidney cells (VERO 76) were used for in vitro culture systems for PRRSV, SIV and PEDV, respectively. Cytotoxicity was established using serial dilutions of oleandrin or PBI-05204. Noncytotoxic concentrations of each product were used either prior to or at 12 h and 24 h following exposure to corresponding viruses. Infectious virus titers were also determined. Results Oleandrin and PBI-05204 demonstrated strong antiviral activity against PRRSV, SIV and PEDV when added prior to or following infection of cells. Determination of viral loads by PCR demonstrated a decline in PRRSV replication reaching 99.57% and 99.79% for oleandrin and PBI-05204, respectively, and decrease of 95.36% and 99.54% in infectivity of progeny virus in PRRSV infected cultures. Similarly, oleandrin tested against SIV and PEDV was effective in near complete inhibition of infectious virus production. Conclusion The research demonstrates the potency of oleandrin and PBI-05204 to inhibit infectivity of three important porcine viruses. These data showing non-toxic concentrations of oleandrin as a single common agent for inhibiting infectivity of the three different porcine viruses tested here support further investigation of antiviral efficacy and possible in vivo use.